UNPLANNED DEVELOPMENT AND OVER EXPLOITATION OF GROUNDWATER IN ZAHEDAN CITY IN THE EAST OF IRAN - Lashkaripour, G. R. (Águas Subterrâneas, 2000)
Zahedan City lies in the most arid area in the eastern part of Iran close to Pakistan border. This city with a population of more than 500,000 has the highest rate of population growth among the big cities of the country. Water demand in the city is estimated at 140 million liters/day in summer. At present, all of water supply in the city is obtained from groundwater. Groundwater is provided from an aquifer with an area of 120 km2. The monitoring of groundwater levels exhibits a decreasing trend of water level. Groundwater pollution and problem in water supply appear to be some of the most important reasons inhibiting the sustainable economic development of the city. The quality of groundwater deteriorated sharply during recent years. The main reasons responsible for the deterioration of water are as follows: (i) Movement of saline water from the east part of the aquifer and interaction in the sweet water aquifer in the west part. (ii) Lowering of the groundwater table, because the wells pumping from groundwater has exceeded natural recharge in the Zahedan basin since 1980. (iii) Rapid growth of the city population in the recent years and aquifer pollution by human activities is serious in this city. (iv) Uncontrolled and unplanned development of the city in western part over the aquifer providing fresh water has led real problem of overdraft or over exploitation. (v) The city has not any sewerage system and it is one of the main factor that increase groundwater pollution. However, liquid wastes may enter into the groundwater, either directly through deep wells or indirectly by percolation. At present, a massive federal project of 191 km pipeline under the Ministry of Power is under construction for drinking water supply from Chahnimah reservoir. At the end of 2000, the majority of the city population will receive water from it.